Systematic study of precursor effects on structure and oxygen reduction reaction activity of FeNC catalysts. (1st November 2021) - Theis, Pascal; Wallace, W. David Z.; Ni, Lingmei; Kübler, Markus; Schlander, Annika; Stark, Robert W.; Weidler, Natascha; Gallei, Markus; Kramm, Ulrike I.
Abstract : In this work, the effect of porphyrin loading and template size is varied systematically to study its impact on the oxygen reduction reaction (ORR) activity and selectivity as followed by rotating ring disc electrode experiments in both acidic and alkaline electrolytes. The structural composition and morphology are investigated by 57 Fe Mössbauer spectroscopy, transmission electron microscopy, Raman spectroscopy and Brunauer–Emmett–Teller analysis. It is shown that with decreasing template size, specifically the ORR performance towards fuel cell application gets improved, while at constant area loading of the iron precursor (here expressed in number of porphyrin layers), the iron signature does not change much. Moreover, it is well illustrated that too large area loadings result in the formation of undesired side phases that also cause a decrease in the performance, specifically in acidic electrolyte. Thus, if the impact of morphology is the focus of research it is important to consider the area loading rather than its weight loading. At constant weight loading, beside morphology the structural composition can also change and impact the catalytic performance. This article is part of the theme issue 'Bio-derived and bioinspired sustainable advanced materials for emerging technologies (part 2)'.